Time factors of clinical effectiveness of mechanical thrombectomy in acute ischemic stroke - A.M. Netliukh; A.A. Sukhanov (Українська Інтервенційна Нейрорадіологія та Хірургія)
It is known that time plays an important role in acute occlusion of large vessels, in particular, the clinical effect of treatment often depends on it. Along with this, there are often delays at the hospitalization stage, the causes of which require analysis and correction. Objective ‒ to analyze the relationship between the severity of the patient’s condition at admission, delays before the start of thrombectomy and the influence of the time factor on the functional outcome at discharge. Materials and methods. Informed consent was obtained from each patient (parent or guardian) enrolled in the study and the study protocol conforms to the ethical guidelines of the Declaration of Helsinki as reflected in a priori approval by the Institutional Ethical Review Board (Institution's Human Research Committee). From January to July 2023 72 patients with acute occlusion of cerebral vessels who underwent thrombectomy at the «1 TMO of Lviv» were examined. Among them there were 40 (55,6 %) men and 32 (44,4 %) women. The age of the patients ranged from 34 to 90 years (on average ‒ 68.4±10.9). Stroke severity was assessed at admission using the National Institutes of Health Stroke Scale (NIHSS) (from 5 to 28 points). The functional capacity of patients was assessed on the modified Rankin scale (mRS) at the time of discharge from the hospital as positive (mRS 0‒3 points) and negative (mRS 4‒6 points). We compared the time from onset of symptoms to admission and from admission to puncture in patients with a positive and negative functional result at the time of discharge, as well as the time from admission to puncture in patients with gross (NIHSS >15 points) and moderately expressed (NIHSS ≤15 points) neurological deficit at admission. mRS was compared between the NIHSS >15 and NIHSS ≤15 groups. Results. The time from onset of symptoms to admission was from 25 to 300 minutes, and the time from admission to puncture ‒ from 30 to 215 minutes. Reduction in time from onset of symptoms to admission (97.9±8.7 min. vs. 131.7±12.6 min, p=0.05) was associated with a positive functional outcome. The time from admission to puncture in this group was also significantly shorter compared to the group of patients with a negative functional result at discharge and amounted to 75.5±4.1 min vs. 94.8±5.7 min, respectively (p=0.01). Patients with gross neurological deficits on admission had a longer period from admission to puncture (on average 91.9±5.9 min) compared to patients with NIHSS ≤15 (77.2±6.1 min, p<0,05). In the group of patients with NIHSS >15 at the time of discharge, an excellent result of mRS (0‒2) was noted in 16.7 % of patients, mRS 3–4 ‒ in 55.5 %, mRS 5–6 ‒ in 27, 8 %; in the NIHSS ≤15 group ‒ in 53.1, 40.6 and 6.3 %, respectively. Conclusions. Factors associated with a positive clinical effect (mRS 0‒3) were early hospitalization from the time of onset of symptoms to the start of surgery without delays in the hospitalization stage. In the group of patients with gross neurological deficit at admission, the period from admission to puncture was longer than in the NIHSS ≤15 group. Patients from the group with moderately pronounced neurological deficits, in the vast majority, have a better functional result at the time of discharge.